Recommendations for the use of oral treprostinil in clinical practice: a Delphi consensus project pulmonary circulation. (March 2017) - Rahaghi, Franck F.; Feldman, Jeremy P.; Allen, Roblee P.; Tapson, Victor; Safdar, Zeenat; Balasubramanian, Vijay P.; Shapiro, Shelley; Mathier, Michael A.; Elwing, Jean M.; Chakinala, Murali M.; White, R. James
Oral treprostinil was recently labeled for treatment of pulmonary arterial hypertension. Similar to the period immediately after parenteral treprostinil was approved, there is a significant knowledge gap for practicing physicians who might prescribe oral treprostinil. Despite its oral route of delivery, use of the drug is challenging because of the requirement for careful titration and management of drug-related adverse effects. We aimed to create a consensus document combining available evidence with expert opinion to provide guidance for use of oral treprostinil. Following a methodology commonly used in business and social sciences (the 'Delphi Process'), two investigators from the oral treprostinil (Freedom) studies created a series of statements based on available evidence and the package insert. The set of 'best practice' statements was circulated to nine other Freedom trial investigators. Their comments were incorporated into the document as new line items for further vote and comment. The subsequent document was put to vote line by line (scale of −5 to +5) and a final statement was drafted. Consensus recommendations include initial therapy with 0.125 mg for treatment na patients, three times daily dosing, aggressive use of antidiarrheal medication, and a strong preference for use of the drug in combination with other approved PAH therapies. This process was particularly valuable in providing guidance for the management of adverse events (where essentially no data is available). The Delphi process was useful to codify investigator experience and subsequently develop investigator consensus about practical issues for physicians who may wish to prescribe oral treprostinil.